2022
DOI: 10.1002/art.42075
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib in Patients With Autoimmune Disease–Related Progressive Fibrosing Interstitial Lung Diseases: Subgroup Analysis of the INBUILD Trial

Abstract: OBJECTIVE: To analyze the efficacy and safety of nintedanib in patients with fibrosing autoimmune disease-related interstitial lung diseases (ILDs) with a progressive phenotype. METHODS: The INBUILD trial enrolled subjects with a fibrosing ILD other than idiopathic pulmonary fibrosis, with diffuse fibrosing lung disease of >10% extent on high-resolution computed tomography, forced vital capacity (FVC) 45% predicted and diffusing capacity of the lungs for carbon monoxide 30%-<80% predicted. Subjects fulfilled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 34 publications
2
32
0
3
Order By: Relevance
“…The pathobiology of progressive fibrosing ILD remains incompletely understood [ 27 ], but these findings support the proposition that fibrosing ILDs show commonalities in the pathobiological pathways that lead to progression of fibrosis [ 14 , 27 30 ] and that nintedanib slows the progression of pulmonary fibrosis irrespective of its aetiology [ 14 , 17 , 29 31 ]. Further support for this hypothesis is provided by subgroup analyses of data from the INBUILD trial that suggested that the effect of nintedanib on FVC decline was consistent irrespective of the underlying diagnosis [ 29 , 30 ]. Subgroup analyses have also shown that nintedanib has a consistent effect on reducing FVC decline in subjects of different ages and disease severities based on FVC, DLco, or staging systems such as the composite physiologic index or GAP index [ 32 37 ].…”
Section: Discussionmentioning
confidence: 86%
“…The pathobiology of progressive fibrosing ILD remains incompletely understood [ 27 ], but these findings support the proposition that fibrosing ILDs show commonalities in the pathobiological pathways that lead to progression of fibrosis [ 14 , 27 30 ] and that nintedanib slows the progression of pulmonary fibrosis irrespective of its aetiology [ 14 , 17 , 29 31 ]. Further support for this hypothesis is provided by subgroup analyses of data from the INBUILD trial that suggested that the effect of nintedanib on FVC decline was consistent irrespective of the underlying diagnosis [ 29 , 30 ]. Subgroup analyses have also shown that nintedanib has a consistent effect on reducing FVC decline in subjects of different ages and disease severities based on FVC, DLco, or staging systems such as the composite physiologic index or GAP index [ 32 37 ].…”
Section: Discussionmentioning
confidence: 86%
“…In the majority of included studies for this meta-analysis, patients were considered non-responsive or refractory to typical immunosuppression, suggesting a separate role for the targeting of other immune-mediated or inflammatory processes for RTX. Current approval of anti-fibrotic therapy for progressive fibrotic lung disease including CTD-ILD warrants consideration as preferred secondary or tertiary therapies for lung fibrosis over RTX [ 55 , 56 ]. Whether anti-fibrotics are preferred over RTX remains debatable but might be more justified by available controlled studies in progressive ILD over currently uncontrolled and mostly descriptive data for RTX [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another large phase III randomized clinical trial included patients with SSc-ILD as part of a wider progressive fibrosing ILD population ( n = 39/663) [36 ▪▪ ]. The results across the autoimmune subset have been presented [37 ▪▪ ]. Considering the evidence for nintedanib, it can be suggested that it significantly reduces the annual decline in FVC in SSc-ILD or progressive fibrosing ILDs including SSc-ILD.…”
Section: Recent Advances In Clinical Management Of Systemic Sclerosis...mentioning
confidence: 99%